A highly sustainable and versatile granulation method of nanodrugs via their electrostatic adsorption onto chitosan microparticles as the granulation substrates - Yang, Yue (2013)
Nanodrugs play important roles in enhancing the sustainability of pharmaceutical manufacturing via their ability to enhance the bioavailability of poorly soluble drugs, resulting in less drug wastage and less mass/energy consumed in their manufacturing. Despite their sustainability enhancement capability, solid dosage form manufacturing of nanodrugs remains lacking from the sustainability perspective. One example is the granulation of nanodrugs prior to tablet preparation, where existing methods (e.g. wet granulation, spray granulation, spray drying) require high energy and time expenses, or are highly intricate often leading to product inconsistencies. Herein we present an alternative nanodrug granulation method via electrostatic adsorption of the nanodrugs onto chitosan microparticles acting as granulation substrates. The method is sustainable involving only mixing of aqueous suspensions of the nanodrugs and substrates under ambient conditions, followed by washing and drying. We investigate the effects of substrate’s physical characteristics and nanodrug to substrate ratio on the nanodrug loading in the granules, content uniformity, nanodrug recovery, and granule flowability. Ciprofloxacin and curcumin nanoplexes prepared by drug–polyelectrolyte complexation are used as the model nanodrugs with neutrally, positively, and negatively charged chitosan microparticles as the substrates. Granules having 25% (w/w) nanodrug loading at 50% (w/w) recovery with good flowability have been successfully prepared.